Theoretical basis of property rights to land (Journal of actual problems of jurisprudence, 2019)
In this article the property rights to the land as a subjective right is protected by law type and amount of the possible behavior of a person or entity as a carrier of one of the proprietary rights to the land. Analysis of the Land Code of the Republic of Kazakhstan shows that the implementation of private land ownership differs from the implementation of state ownership. Recommendations and proposals for improvement of the legislative system in the Republic of Kazakhstan have been drawn up on the basis of analysis of the theories, the historical experience of Kazakhstan and other countries, and the applicable laws in Kazakhstan.